Open Science: A Candid Conversation. Issue 2 (May 2019) - Smith, Kendal N.; Makel, Matthew C.
In response to concerns about the credibility of many published research findings, open science reforms such as preregistration, data sharing, and alternative forms of publication are being increasingly adopted across scientific communities. Although journals on giftedness and advanced academic research have already implemented several of these practices, they remain unfamiliar to some researchers. In this informal conversation, Kendal Smith and Matthew Makel discuss how they came to know and use open science practices, the values of open science, benefits and objections, and their future aspirations for open science practices in gifted education research. Their conversation aims to help make open science practices more understandable and actionable for both early career and established researchers.